HAEMATOLOGICAL CHANGES INDUCED BY SHORT - TERM EXPOSURE TO COPPER IN THE INDIAN FRESHWATER FISH, NOTOPTERUS NOTOPTERUS (PALLAS) - V. S. BARAD,; R. S. KULKARNI, (The Bioscan, 2010)
The normal ranges of blood chemistry and the effect of copper sulfate was studied in Indian fresh water fish, Notopterus notopterus. The blood serum biochemical components like, hemoglobin, proteins, urea, urea nitrogen, cholesterol, and glucose levels were determined during the phase of reproductive cycle. Toxic level (LC50) of copper sulfate was found to be 30ppm. Under this concentration (30ppm) after exposure to 96hr the haematological parameters such as glucose, protein, urea, urea nitrogen, cholesterol, creatinine and haemoglobin content were estimated in the blood serum. A significant decrease (p < 0.001) in the biochemical profile such as protein, glucose, urea, urea nitrogen and creatinine were observed; where as haemoglobin (p < 0.001) and cholesterol (p < 0.01) levels in the blood of exposed group was significantly (p < 0.001) higher than that of the control group. The results suggest that the reduction in the above biochemical levels of blood serum may be because of stress due to copper concentration.